Penerapan Kompetensi Guru BK oleh Guru Muda dalam Melaksanakan Praktikum Pengalaman Lapangan Sekolah (Studi terhadap Mahasiswa PPLBK Sekolah Angkatan 2010 STKIP PGRI Sumatera Barat) - Handoko, Ricky - (Bimbingan dan Konseling, 2014)
This research is motivated by the presence of some young teachers who look sloppy, no young teachers who get angry when in the classroom, there are young teachers who are not serious in providing material services, there are young teachers who do not come to school on time, there was a young teacher who smoke around the school, there is a young teacher in making RPL confusion, there are young teachers who do not make a service program, there are young teachers who do not recognize learners. The purpose of this study describe: 1) Application of pedagogical competence by young teachers. 2) Application of personal competence by young teachers. 3) Implementation of social competence by a young teacher. 4) Application of the professional competence of the young teacher.This type of research is descriptive quantitative research with the entire student population of Guidance and Counseling 2010 which has completed the Practicum Field Experience in Implementing School in the academic year 2013/2014 which amounted to 197 and 66 samples. Sampling using incidental sampling technique. The instrument used for data collection in the form of a questionnaire. To analyze the data the application of Guidance and Counseling teacher competence by young teachers using percentage analysis techniques.The results of data analysis showed that: (1) The application of the pedagogic competence in the category applied. (2) Application of personal competence in the category applied. (3) The application of social competence in the category applied. (4) The application of professional competence in the category applied. So based on the results of research in general application of the competency of teachers Guidance and Counseling by a young teacher has been implemented well by the young teacher class of 2010 STKIP PGRI West Sumatra. The results of this study recommended to the young teacher, student of Guidance and Counseling, Guidance and Counseling studies program managers, and further research.